Multimodal representations and new literacies in the digital age - Novoa Echaurren, Angela (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
This article discusses the research literature related to new forms of representations and new literacies in contemporary communication environments. In a digitally-mediated world the conventions of contemporary communication offers challenges to the way education is envisioned either in primary, secondary and higher education settings. The increased access to Information and Communication Technologies (ICT) has provided transformations in the ways in which people construct meanings, represent the world, and communicate with others. Users of ICT (in particular of mobile devices) have developed multiple and modular forms of thinking and communicating. Given this context, the ways in which students learn and socialize has become more complex.
Keywords: New representations; digital literacies; ICT